Plasminogen/plasmin influence on platelet aggregation - Roka-Moya, Y.M.; Zhernossekov, D.D.; Grinenko, T.V. (Вiopolymers and Cell, 2012)
Aim. Determination of the influence of Glu- and Lys-plasminogen/ plasmin on the platelet aggregation induced by different agonists. Methods. Platelet aggregometry. Spectrophotometry. Results. We have shown the inhibitory effect of Lys-plasminogen on human platelet aggregation. The pro-enzyme action is related to the second wave of aggregation. The inhibitory effect of Lys-plasminogen possesses dosedependent manner in case of thrombin-induced aggregation. The inhibitory effect of pro-enzyme with ristocetin as an inductor has not been observed. Glu-plasminogen and plasmin do not influence on platelet aggregation under studied conditions. A serine protease inhibitor aprotinin does not change the inhibitory effect of Lys-plasminogen. Conclusions. The results proved the inhibitory effect of Lys-plasminogen on thrombin- and collagen-induced platelet aggregation. The absence of inhibitory effect of Lys-plasminogen in the case of ristocetin-induced aggregation leads us to conclusion, that GP Ib/IX is not involved into the inhibited aggregation pathway. The unchanged inhibitory effect of Lys-plasminogen in the presence of aprotinin excludes plasmin participation in the inhibitory phenomenon. Keywords: platelet aggregation, plasminogen, plasmin.